Isolation and Activity Test of Antimicrobial Endophytic Bacteria from Leaf Salam (Syzygium polyanthum Wight) - Irdawati Yahya; Linda Advinda; Fitri Angraini (Bioscience, 2017)
Abstract -- Endophytic bacteria are microorganisms that exist in the system of plant tissues such as leaves, twigs, roots and they can form colonies without causing damage to the plant. The endophytic bacteria may produce secondary metabolites in accordance. One potential medicinal plant has endophytic bacteria are plant greeting (Syzygium polyanthum Wight). Part of the plant Salam particularly frequently used is part of the leaf, which serves as an antibacterial and antifungal. Because the leaves contain compounds bay leaf tannins, flavonoids and essential oils. The porpuse of this research was to find of to obtain isolates of endophytic bacteria and determine the antimicrobial activity of bay leaf (Syzygium polyanthum Wight).This research is descriptive that has done on January - February 2015 of Microbiology Laboratory at Biology Departement FMIPA, UNP. The parameters observed in the determination of isolates is a form colonies, colonies edge, elevation colonies, colony color, and Gram staining of  leaves (Syzygium polyanthum Wight). The antimicrobial activity was observed with the formation zone of inhibition around the paper disc. Obtained were 11 isolates of endophytic bacteria from leaves, 5 isolates of endophytic bacteria have the ability to produce antimicrobial.Isolates had the highest antimicrobial activity that isolates DSA 1-1 with a 6.42 mm diameter inhibition zone. Keywords: antimicrobial, endophytic bacteria, bay leaf.